Urgensi Pesero Komanditer Memberi Persetujuan kepada Pesero Pengurus dalam Melakukan Tindakan Kepemilikan - Tanriawan, Florensya Octavia; Aprilianda, Nurini; Susilo, Hariyanto (JURNAL USM LAW REVIEW, 2023)
This study aims to explore and analyze the urgency of the approval of limited liability companies in ownership actions carried out by management partners in limited liability companies. The urgency of this research lies in developing an understanding of the role and protection of the rights of limited partners in safeguarding their interests and investments. The research method used is normative legal research with statutory and conceptual approaches. The results of the study show the urgency of the approval of limited partnership partners with managing partners in the act of ownership is essential to protect the rights and interests of limited partners, with effective legal protection, written agreements, and good communication between parties to avoid disputes and ensure the sustainability of the company. The novelty of the research lies in an in-depth analysis of the legal protection for limited liability companies and the impact of own actions without the approval of limited partners, which provides a more comprehensive understanding of the importance of limited partnership approval in the legal and business context so that this research is expected to open deeper insights into the mechanisms and legal implications of acceptance given by limited partners as a form of protection for investors and financial conditions in limited liability companies. Tujuan penelitian ini adalah menggali dan menganalisis urgensi persetujuan Pesero Komanditer dalam tindakan kepemilikan yang dilakukan oleh Pesero Pengurus dalam perseroan komanditer. Urgensi penelitian ini terletak pada pengembangan pemahaman mengenai peran dan perlindungan hak Pesero Komanditer dalam menjaga kepentingan dan investasi mereka. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan urgensi persetujuan pesero komanditer kepada pesero pengurus dalam tindakan kepemilikan adalah penting untuk melindungi hak dan kepentingan pesero komanditer, dengan perlindungan hukum yang efektif, perjanjian tertulis, dan komunikasi yang baik antar pihak guna menghindari perselisihan dan memastikan keberlanjutan perseroan. Novelty penelitian terletak pada analisis mendalam mengenai perlindungan hukum bagi pesero komanditer dan dampak tindakan kepemilikan tanpa persetujuan pesero komanditer, yang memberikan pemahaman yang lebih komprehensif tentang pentingnya persetujuan pesero komanditer dalam konteks hukum dan bisnis. Sehingga penelitian ini diharapkan membuka wawasan yang lebih dalam mengenai mekanisme dan implikasi hukum dari persetujuan yang diberikan oleh pesero komanditer sebagai bentuk proteksi terhadap investasi dan kondisi keuangan dalam perseroan komanditer.